Clinical profile of sepsis and choice of antimicrobials in babies admitted to special newborn care unit Kalaburagi - Bhosgi, Revanasiddappa; Harwalkar, Kirankumar (International Journal of Contemporary Pediatrics, 2021)
Background: Sepsis is one of the common clinical conditions seen in neonates. Sepsis being major cause of neonatal morbidity and mortality in neonates, early recognition and treatment with antibiotics remains a mainstay of NICU protocols for neonatologists. Methods: It is a hospital based retrospective study conducted from July 2019 to February 2020 in GIMS, Kalaburagi. Neonates with suspicion of clinical sepsis were investigated for complete blood count (CBC), C-reactive protein (CRP) and blood culture (BC). Antibiotics were started based on CBC and CRP reports, or on high index of clinical suspicion. Based on common organisms isolated in previous 3 months statistics, antibiotics were decided. On confirmation by blood culture, antibiotics were changed as per blood culture report. Results: Out of 100 neonates, CRP was positive in 80 (70%) neonates, BC showed growth among 24 (24%) neonates. Although neonates had clinical sepsis, CRP was negative in 20 (10%), 76 (76%) did not show any kind of growth on BC. Mortality was seen in 04 (5%) neonates with only CRP positive, 02 (08%) neonates with only BC growth, 02 (10%) neonates with both CRP positive and BC growth, 02 (03%) neonates with CRP positive but no growth on BC. Clinical features were from subtle to severe. Conclusions: Although CRP and blood culture confirmation remains one of the main diagnostic parameter in sepsis, as mortality is seen among neonates with negative blood parameters, high index of clinical suspicion is essential to treat sepsis at an early stage.